A low-cost open-source handheld LiDAR-based automated understory timber stand surveying device. (October 2022) - Bessell, Brandt; Singh, Aditya
Graphical abstract: Abstract: Timber stand inventories are critical for making management decisions in both commercial and conservation related forestry applications. When taking these inventories, the most critical characteristics to record are diameter at breast height (DBH), stand density, tree height and tree species. As discovered in prior research, a relatively inexpensive device, which hereby will be referred to as AutoTSI (short for Automatic Timber Stand Inventory), can be assembled and deployed in the field to take accurate measurements of diameter at breast height (DBH) for timber stand sample plots in a short amount of time compared to the traditional method of manually measuring these trees. The specified range and angle of resolution of the sensor allows for estimation of stand density and basal area. Each element of both the hardware and software is modular by design allowing the user to customize according to whatever sensors may be readily available to the user. In silviculture research, methodical collection, and analysis of geometric measurements of trees is essential for developing land management plans that optimize biomass production, biodiversity, and other desired characteristics in a forest environment making this device useful to both tree farmers and researchers.